"I Had to Reinvent My Jewishness": Personal and Professional Identity Perceptions of Jewish Culture Teachers from the Former Soviet Union. Issue 2 (3rd April 2022) - Binhas, Adi; Yaniv, Iris
ABSTRACT: This article deals with the perceived professional and personal identity of Israeli public-school teachers of subjects related to Jewish culture who have immigrated from the former Soviet Union (FSU). Our research question was: What was the impact of the emigration from the FSU on the teachers' Jewish-Israeli identity construction, and how did this process reflect on their professional self-perception as teachers of Jewishness-related subjects? We found that the development of the teachers' individual Jewish identity had a considerable impact on shaping their educational approach to teaching Jewish cultural subjects.